بلاغة القناع في القصة الرقمية التفاعلية " تحفة النظّارة في عجائب الإمارة " لمحمد سناجلة - خاوة, فاطمة الزهرة; عماري, فطوم; خلفاوي, نورة (جامعة الوادي - University of Eloued, 2023)
الملخص: يتمحور البحث حول دراسة الوظيفة البلاغية لتقنية القناع في الأدب الرقمي التفاعلي من خلال قصة (تحفة النظارة في عجائب الإمارة) لمحمد سناجلة، وهي قصة رقمية تفاعلية استعمل المؤلف فيها تقنية التقنع متقمّصًا شخصية ابن بطوطة ومحاكيًا رحلته، وقد اختار المؤلف مدينة دبي كنموذج مكاني موازي للأماكن التي سافر إليها ابن بطوطة قديما. جاءت هذه الدراسة لتكشف عن تجليات القناع وبلاغة توظيفه على مختلف المستويات الفنية للقصة، على المستوى التصويري، وعلى مستوى العتبات النصية، واللغة والأسلوب كذلك. The research focuses on studying the rhetorical function of the mask technique in interactive digital literature through the story (The Masterpiece of Spectacles in the Wonders of the Emirate) by Muhammad Sanajleh, which is an interactive digital story in which the author used the masking technique impersonating Ibn Battuta and simulating his journey. The author chose Dubai as a spatial model parallel to other places. Where Ibn Battuta traveled in the past. This study came to reveal the manifestations of the mask and the rhetoric of its employment on the various artistic levels of the story, on the pictorial level, and on the level of textual thresholds, language and style as well.
نقد حديث ومعاصر
Keywords: القناع، الأدب الرقمي التفاعلي، ابن بطوطة، محمد سناجلة; The Mask, Interactive Digital Literature, Ibn Battuta, Muhammad Snajleh